A comprehensive guide to sign language interpreting in Europe - Wit, Maya de (Países Bajos : Editora M. de Wit, 2016)
Sign Language Interpreting in Europe, 2020 edition gives an overview of the organizations, educational programs, and employment situations of sign language interpreters in Europe. First published in the year 2000, this year's guide is the sixth updated edition.Qualitative and quantitative survey data allows readers to do an in-depth analysis of the current state of affairs in the European field of sign language interpreting. This study also allows you to make comparisons between individual countries and to trace current trends.Sign Language Interpreting in Europe is based on a 2020 survey, held among national organizations of sign language interpreters in European countries and regions. The findings of the survey were supplemented with information collected from several publications on sign language interpreting throughout Europe.
Ofrece una visión general de las organizaciones, programas educativos y situaciones laborales de los intérpretes de lengua de señas en Europa. La guía de esta actualizada. Los datos de encuestas cualitativas y cuantitativas permiten a los lectores realizar un análisis en profundidad del estado actual de las cosas en el campo europeo de la interpretación en lengua de señas. Este estudio también permite hacer comparaciones entre los países individuales y rastrear tendencias actuales. La interpretación en lengua de señas en Europa se basa en una encuesta de 2020, realizada entre organizaciones nacionales de intérpretes de lengua de señas en países y regiones europeas. Los hallazgos de la encuesta fueron complementados con información recopilada de varias publicaciones sobre la interpretación en lengua de señas a lo largo de Europa.
Appendices
Keywords: LENGUAGE DE SIGNOS -- EUROPA; EDUCACIÓN; DISCAPACIDAD AUDITIVA; LENGUAS DE SEÑAS; SIGN LANGUAGE INTERPRETING I -- EUROPE